ELECTRONIC EXCITATION DECAY IN LiNbO3:Yb3+ CRYSTALS IN THE PRESENCE OF PAIR IMPURITY CENTERS - G. G. Demirkhanyan; H. G. Demirkhanyan; R. B. Kostanyan
The influence of phenomenon of electronic excitation trapping, caused by processes of nonradiative redistribution of electronic excitation energy (NREEE) in impurity subsystem, on kinetic characteristics of excitation decay in LiNbO3:Yb3+ crystals is investigated. Probabilities of elementary acts of the NREEE are calculated. On the basis of the simplest model the kinetic characteristics of electronic excitation decay with taking into account the presence of both the single and pair impurity centers in crystalline matrix in the case of small concentration of impurity ions are calculated. The dependences of electronic excitation lifetime and luminescence quantum yield on the impurity concentration and pump power are determined.
Keywords: Physics; Materials science